Pengaruh Media Video Tutorial terhadap Motivasi Belajar Siswa TKJ SMK Ypkk Limbung Gowa dalam Pelajaran Sistem Komputer - Rezki Fakhriyah; Alifya Nfh; Ninik Rahayu Ashadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the effect of tutorial video media on the learning motivation of TKJ students at SMK YPKK Limbung Gowa in the Computer Systems subject. The type of research used is ex post facto research, which is included in quantitative non-experimental research. The results of the study indicate that the level of use of tutorial video media among Grade X TKJ students at SMK YPKK Limbung Gowa is in the moderate/fairly high category. This is shown by the average score of 48.67, as well as the categorization results where the majority of students (80%) are in the moderate category. This indicates that tutorial video media has been used quite effectively in the learning process. In addition, the level of students’ learning motivation in the Computer Systems subject is in the high category, with an average score of 51.13. However, the distribution shows that most students (53.3%) are in the moderate category, so it can be concluded that students’ learning motivation is generally good but not yet optimally distributed. The study also found that there is a positive and significant effect between the use of tutorial video media and students’ learning motivation. This is proven by the results of the t-test with a significance value of 0.001 0.05 and a t-count value of 3.927. Furthermore, the coefficient of determination test results show that tutorial video media contributes 32.2% to students’ learning motivation, while the remaining percentage is influenced by other factors outside the scope of this study.